A durable response to programmed cell death 1 blockade in a multidrug-resistant recurrent ovarian cancer patient with HLA-B44 supertype: A case report - Luo, Xukai; Sun, Yating; Li, Jiajia; Jiang, Qidi; Yuan, Lei; Li, Ting; Chen, Mo; Yao, Liangqing (Frontiers in Immunology, 2022)
Relapsed/refractory ovarian cancer, especially platinum resistance recurrence, remains a major therapeutic challenge. Here, we present the case of a patient with recurrent ovarian clear cell carcinoma (OCCC), who failed to respond to multiline chemotherapy and target therapy but achieved a completed response (CR) with programmed cell death l (PD-1) inhibitor treatment. The overall survival (OS) was 57 months and recurrence-free survival (RFS) was 32 months after immunotherapy, which was counting. Meantime, molecular testing results revealed that traditional biomarkers for immunotherapy, including PD-L1 expression, microsatellite instability (MSI) and tumor mutational burden (TMB), were negative.HLA-B44 (B*18:01) supertype was confirmed by sequence-based HLA typing. This case suggested that ovarian cancer patients with multidrug-resistant may still derive the long-term benefit of the PD-1 inhibitor, even if PD-L1 is negative. HLA-B44 supertype may be the potential predictor for immunotherapy in OCCC.